Princess power: Deconstructing the influence of popular culture on local traditions in a novel - Muhammad Nasir; Rahayu Puji Haryanti; Desri Maria Sumbayak (Universitas Syiah Kuala, 2024)
The study employed a descriptive methodology with a cultural perspective, with a key focus on dissecting the novel Princess: A True Story of Life Behind the Veil in Saudi Arabia by Jean Sasson published in 1993 to explore the impact of popular culture on the identity of Saudi women, focusing on the princesses within the royal palace. The cultural environment of Saudi Arabia presents a complex scenario for women as they reconcile traditional Islamic values with pervasive Westernized influences. This inquiry scrutinized how popular culture, introduced through migration and media exposure, molded Saudi womens attitudes and actions, particularly those of the royal lineage. This novel is the source of data for the research. The analysis focused on themes, representations, and cultural significance. It examined language, imagery, and narratives to uncover meanings and relate them to broader societal issues, ultimately revealing how popular culture reflects or challenges prevailing ideologies. The findings revealed Sultanas struggle to balance her Saudi princess identity with Western influences, revealing the complexities of cultural exchange, marriage practices, and societal expectations in both Western and Islamic contexts. Sassons narrative highlights how global influences, particularly Western culture, shape perceptions and interactions, enriching yet complicating societal norms. Vivid depictions of gender roles, sensory experiences, and emotional responses underline the ongoing struggles women face in patriarchal societies. These stories provide an understanding of the intersections of culture, gender, and identity, reflecting personal journeys while echoing broader themes of empowerment, resistance, and evolving cultural identities in a globalized world.